Basis of Virulence in a Panton-Valentine Leukocidin-Negative Community-Associated Methicillin-Resistant Staphylococcus aureus Strain - Chen, Yan (J Infect Dis, 2015)
Community-associated (CA) infections with methicillin-resistant Staphylococcus aureus (MRSA) are on a global rise. However, analysis of virulence characteristics has been limited almost exclusively to the US endemic strain USA300. CA-MRSA strains that do not produce Panton-Valentine leukocidin (PVL) have not been investigated on a molecular level. Therefore, we analyzed virulence determinants in a PVL-negative CA-MRSA strain, ST72, from Korea. Genome-wide analysis identified 3 loci that are unique to that strain, but did not affect virulence. In contrast, phenol-soluble modulins (PSMs) and the global virulence regulator Agr strongly affected lysis of neutrophils and erythrocytes, while α-toxin and Agr had a major impact on in vivo virulence. Our findings substantiate the general key roles these factors play in CA-MRSA virulence. However, our analyses also showed noticeable differences to strain USA300, inasmuch as α-toxin emerged as a much more important factor than PSMs in experimental skin infection caused by ST72.